The Role of Family Ownership and Management in Shaping Corporate Financial Outcomes - Baihaki Hylmi Habibi; Jazuli, A Muhamad (Jurnal Management Risiko dan Keuangan, 2025)
This study aims to examine the influence of family ownership and family involvement in management on financial performance. The study focuses on manufacturing firms listed on the Indonesia Stock Exchange (IDX) during the 2022–2023 period. This research employs a quantitative approach, with a sample selected through purposive sampling, resulting in a total of 111 companies. Secondary data from financial reports were analyzed using multiple linear regression with the SPSS version 27 program. The results indicate that family ownership has a marginal positive influence on financial performance. Conversely, family involvement in management was not found to have a significant effect and tended to show a negative impact. These findings imply that to maximize performance, family manufacturing firms need to strengthen their corporate governance structures.